(untitled) (Applied Biological Research, 2018)
The present study was conducted on 36 samples of thyroid glands of Bakerwali goat, divided into 3 groups based on the age of animals viz., prepubertal (<1 year), pubertal (2-3 years) and senile (>5 years). Thyroid gland was located on the dorsolateral aspect of trachea. The gland was bilobed, reddish brown in colour, elongated and elliptical in outline. The right lobe of gland extended from posterior extremity of larynx to 5th tracheal ring, while left lobe extended from extremity of larynx to 7th tracheal ring. The two lobes were connected by isthmus around the ventral aspect of trachea and position varied between 5th and 6th tracheal ring. The mean length of left lobe was larger than right lobe in all the age groups. The biometrical parameters increased with the advancement of age. The isthmus connected the caudal poles of two lobes of gland. The isthmus was glandular in young animals and was becoming fibrous in older ones.